EFEKTIVITAS PENGGUNAAN VIDEO PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN FIQIH - Riza Faishol; Bey Arifin Sidon; Taufiki Rochman; Muh. Barid Nizarudin Wajdi (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2023)
Fiqh education at MTs Darul Amien Jajag often relies on conventional media, which tends to be less engaging and leads to low student achievement. In an effort to improve the quality of education, teachers face the challenge of incorporating more modern and engaging media, such as video learning. This study aims to measure the effectiveness of using video learning to enhance students' learning outcomes in the Fiqh subject. The research employed a Quasi-Experimental method with a pretest-posttest control group design. The population consisted of eighth-grade students at MTs Darul Amien Jajag, with class VIII A as the experimental group and class VIII B as the control group. The results indicate that the use of video learning significantly improved student learning outcomes. This is evidenced by the significant difference between pretest and posttest scores in the experimental class compared to the control class. The findings suggest that video media can be an effective alternative for improving the quality of Fiqh education.